Enhancing spatial skills through mechanical problem solving. (October 2021) - Munoz-Rubke, Felipe; Will, Russell; Hawes, Zachary; James, Karin H.
Abstract: Higher spatial skills are associated with increased interest, performance, and creativity in STEM fields (Science, Technology, Engineering, Mathematics). However, evidence for causal relations between spatial skills and STEM performance remains scarce. In this study, we test the extent to which mechanical problem solving, a spatially demanding STEM activity, facilitates spatial performance. Participants (N = 180) were randomly assigned to one of four training conditions: mechanical reasoning with a hands-on component; mechanical reasoning without a hands-on component; an active control condition involving spatial training with cross-sectioning; and an active control group involving a reading exercise. All participants were tested immediately before, after, and one-week following training. Both mechanical conditions were associated with enhanced spatial visualization performance, an effect that was similar for both conditions and remained stable across immediate and delayed post-tests. These findings suggest that mechanical problem solving is a potentially viable approach to enhancing spatial thinking. Highlights: Mechanical problem solving is a spatially demanding STEM activity. Effects of mechanical problem solving training on spatial skills were evaluated. Engaging in mechanical problem solving enhanced spatial visualization performance. Gains in spatial skills remained stable across immediate and delayed post-tests. Mechanical problem solving could be a viable approach to enhance spatial thinking.